Facial burn in children: a review - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2023)
Burns are a common cause of injury among children. Children with facial burns often experience pain, regardless of the cause, size, or depth of the burn injury. Burns in the facial area may lead to fatal consequences because of the involvement of the upper airway and cosmetic deformity of the face. Major burn injury in the facial area remains a significant cause of morbidity and mortality in children. Burn scars on the face in children may disturb the self-image and psychosocial processes. Multi-disciplinary approaches and advances in burn care are often helpful to manage the burn injury in children and increase the survival of the patients. Pain has adverse emotional and physiological impacts, and adequate pain control is an important factor in improving outcomes. The goal of the treatment of facial burns in children is to achieve a good aesthetic outcome and also normal head movement with neck mobilization.